One-pot hydrothermal synthesis of highly dispersed, phase-pure and stoichiometric lead zirconate - Apinpus Rujiwatra (2018)
Phase-pure and stoichiometric lead zirconate powders consisting of submicro- to micrometer-sized particles were successfully synthesized via a simple, one-pot hydrothermal technique at moderate temperatures and short reaction times. High concentration of potassium hydroxide mineralizer was necessary in the formation of well-crystalline lead zirconate. The type of zirconium precursor, reaction temperature and time showed apparent influences over particle shape, size and distribution. Transmission electron microscope was used to confirm the crystallographic setting of the prepared lead zirconate. © 2006 Elsevier B.V. All rights reserved.